Identification of Formalin and Bacterial Contamination in White Tofu at PD Pasar Surya Traditional Market in Surabaya - Tarissa Ayuni Andriyanto; Ratna Yulistiani (AJARCDE (Asian Journal of Applied Research for Community Development and Empowerment), 2026)
The misuse of formalin and high levels of microbial contamination in tofu are still commonly found today, partly due to poor hygiene and sanitation practices among vendors. This study aims to identify the misuse of formalin, levels of bacterial contamination, and Escherichia coli contamination resulting from the hygiene and sanitation conditions of tofu vendors at the Traditional Market in the East Branch of PD Pasar Surya, Surabaya. This study employed an exploratory and descriptive survey method using a cross-sectional approach, involving observations and interviews with 23 white tofu vendors at the Traditional Market in the East Branch of PD Pasar Surya, Surabaya. The analyses conducted included qualitative formalin testing, Total Plate Count (TPC) testing, and Escherichia coli contamination testing using the Most Probable Number (MPN) method. The relationship between vendors’ sanitation conditions and levels of bacterial contamination and E. coli contamination was assessed using a chi-square test at a 5% significance level. Laboratory results revealed that 100% of all samples (23 out of 23 samples) tested negative for formalin. Approximately 8.69% (2 out of 23 samples) exhibited TPC values exceeding the SNI 01-3142-1998 quality standards (ranging from 1,0 x 10? to 1,2 x 10? colonies/g). Furthermore, 39% (9 out of 23 samples) tested positive for Escherichia coli contamination (ranging from 3.6 to 28 MPN/g). A significant correlation (p<0,05) was found between hygiene-sanitation and TPC, whereas no significant correlation (p>0,05) was observed for Escherichia coli contamination in white tofu sold in the Traditional Markets of the Eastern Branch Region of PD Pasar Surya Surabaya. Contribution to Sustainable Development Goals (SDGs):SDG 2: Zero HungerSDG 3: Good Health and Well-BeingSDG 6: Clean Water and SanitationSDG 12: Responsible Consumption and Production